A review on the role of Epigenetics in Psychiatry: Etiology, contemporary medicine and future perspectives - Oshin, Sadia Afrin (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.